1996
DOI: 10.1007/s004410050591
|View full text |Cite
|
Sign up to set email alerts
|

Development of T-lymphocyte subpopulations in the postnatal chicken oviduct

Abstract: Postnatal development of t-cell subpopulations in the oviduct was investigated in the Dekalb strain of the White Leghorn chicken by using an immunohistochemical method. T-lymphocytes first infiltrated the oviduct at 5 weeks. The number of T cells peaked at 15 weeks in the magnum, isthmus and uterus, and at 19 weeks in the infundibulum and vagina. The epithelium of the oviduct contained both granular and agranular lymphocytes. TcR1+ cells were predominant in the epithelium, whereas TcR2+ cells were more numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…2 -3). Khan et al (1996Khan et al ( , 1999 similarly reported that the spermhost glands of White Leghorn chickens were tubular, and distributed in the lamina propria.…”
Section: Sperm Host Glandsmentioning
confidence: 99%
“…2 -3). Khan et al (1996Khan et al ( , 1999 similarly reported that the spermhost glands of White Leghorn chickens were tubular, and distributed in the lamina propria.…”
Section: Sperm Host Glandsmentioning
confidence: 99%
“…These data suggest an age-related development of LGLs in these organs. Age-dependent changes of T lymphocytes (agranular) have also been reported in the chicken oviduct (Khan et al, 1996a) and intestine (Lillehoj and Chung, 1992;Vervelde and Jeurissen, 1993). In the present study, LGLs were not abundant in the glandular part.…”
Section: Discussionmentioning
confidence: 41%
“…During our previous study into the development of a T-cell subpopulation, the presence of LGLs was observed in the oviducal epithelium of chickens (Khan et al, 1996a). In the present work, we investigated the distributional changes of LGLs in the different segments of the oviduct from 1-d-old to 78 weeks and the influence of oestrogen on these cells.…”
Section: Introductionmentioning
confidence: 94%
“…These dynamic changes in the frequency and distribution of Igs-containing plasma cells were also observed in the Harderian gland, cecal tonsil and trachea of our previous studies [14]. The thymus is responsible for the production of T-lymphocytes subsets in the chicken [18] not Igs-containing plasma cells, however existence of statistically higher IgG-and IgM-positive cells in the thymus of the present study indicates that the B lymphocytes infiltrated in the thymus via blood circulation and differentiated into Igs-containing plasma cell for local defensive function as T-lymphocytes subpopulation do in the bursa of Fabricius [19], which is the homing organ for B lymphocytes.…”
Section: Thymusmentioning
confidence: 53%